GIS applications in agriculture . - Clay, Sharon A. [ (Sharon Ann)] (GIS applications in agriculture, 2011)
We are entering a new era in production agronomics. Agricultural scientists the world over call for the development of techniques that simultaneously increase soil carbon storage and reduce agriculture's energy use. In response, site-specific or precision agriculture has become the focus and direction for the three motivating forces that are changing agriculture today: the expanding capacity of personal computers, the molecular biology revolution, and the recent developments in information technology such as the increasing use of geographical information systems (GIS).Using mathematics, ..